My Pine Is Under Attack—What Should I Do? - Jiri Hulcr (EDIS)
This guide is intended to help tree owners and Extension personnel in Florida and the adjacent southeastern region make decisions about backyard pine trees that display signs of attack by wood borers. The 3-page pictorial guide will help determine whether beetles have attacked a pine tree, how far along the attack has progressed, and what to do about it. There are many sources of pine stress other than insects, so for complete advice, please contact your county Extension agent or post your question at the Tree Health Diagnostics Forum at the University of Florida website. Written by Jiri Hulcr and published by the School of Forest Resources and Conservation, May 2016.